Microsatellite-Based Genetic Diversity Among Three Duck Populations in Sumatera Island - Dyah Maharani; Dwi Nur Happy Hariyono; Jafendi Hasoloan Purba Sidadolog; Sunghyun Cho; Prabuddha Manjula; Dongwon Seo; Nuri Choi; Jun Heon Lee (Buletin Peternakan, 2021)
This study aimed to determine the genetic diversity among three duck populations (Bayang, Pegagan, and Pitalah) reared in Sumatera island, Indonesia, using microsatellite markers. Genetic diversity among populations (n = 90) was determined using 22 microsatellite markers, based on several indices: number of alleles (Na), observed heterozygosity (Ho), expected heterozygosity (He), polymorphism information content (PIC), and Wright’s F-statistics ( ). The total number of alleles detected across loci was 121. The Na per locus ranged from 2 (APH24, CAUD128, and CAUD009) to 18 (CAUD048 and CAUD040). The mean Ho (0.429) dan He (0.509) indicated that the level of genetic diversity among populations was moderate, while the mean PIC (0.46) suggested that the tested loci were informative for assessing genetic diversity. The mean F-statistics ( ) were 0.148, 0.198, and 0.060, respectively. The  value indicated that the level of genetic differentiation among populations was moderate. The results confirms a moderate genetic diversity among populations, which could be beneficial for designing conservation and utilization of the local ducks in Sumatera island.